DENDRITIC CELLS WITH TGF-ß1 and IL-2 DIFFERENTIATE NAÏVE CD4+ T CELLS INTO ALLOANTIGEN SPECIFIC AND ALLOGRAFT PROTECTIVE FOXP3+ REGULATORY T CELLS - Yang, Hua (2012)
BACKGROUND: Naturally occurring, thymic-derived Foxp3+CD25+CD4+ regulatory T cells (natural Tregs) are pivotal for the maintenance of self-tolerance. Natural Tregs, however, are sparse and lack alloantigen specificity and these properties pose challenges for their use in clinical transplantation. METHODS: We established mixed leukocyte reaction (MLR) with dendritic cells (DCs) as stimulators and CD4+ T cells as responders and supplemented the MLR with IL-2 and TGF-β1, and investigated whether DCs+ IL-2 +TGF-β1 differentiate the polyclonal CD4+ cells into alloantigen specific and allograft protective Tregs. RESULTS: We found a greater than a ten-fold increase in Foxp3+ CD25+ subpopulation (P<0.01) following stimulation of BALB/c CD4+ cells with C57BL/6 (B6) CD11c(+) DCs + IL-2 + TGF-β1 in the MLR. Levels of TGF-β1 mRNA (P=0.01) and the ratios of TGF-β1 mRNA to granzyme B mRNA (P=0.0003) and Foxp3 mRNA to granzyme B mRNA (P<0.01) were higher in alloantigen induced Tregs compared to natural Tregs. Alloantigen induced Tregs suppressed MLR at a 16:1 responder to suppressor ratio whereas natural Tregs suppressed at 4:1. Suppression by alloantigen induced Tregs was alloantigen specific and was observed at the level of responder cells and at the level of stimulator cells. In a fully H-2 mismatched, non-lymphopenic, immunocompetent mouse islet transplantation model, alloantigen induced Tregs but not natural Tregs prolonged survival of islet allografts without any other immunosuppressive therapy (P=0.0003), and the protection was alloantigen specific. CONCLUSIONS: A combination of CD11c(+) DCs, IL-2 and TGF-β1 may help differentiate naïve, high abundant CD4+ T in to alloantigen specific and allograft protective Foxp3 + Tregs.